Mutual coupling in MIMO wireless systems a rigorous network theory analysis. - Wallace, J.W.
A new framework for the analysis of multiple-input multiple-output (MIMO) wireless systems is introduced to account for mutual coupling effects in the antenna arrays. The multiport interactions at transmit and receive are characterized by representing the channel using a scattering parameter matrix. A new power constraint that limits the average radiated power is also introduced. The capacity of the MIMO system with mutual coupling is defined as the maximum mutual information of the transmit and receive vectors over all possible transmit signaling and receive loading. Full-wave electromagnetic antenna simulations combined with a simple path-based channel model are used to demonstrate the utility of the method.
Keywords: MIMO wireless systems; Antenna arrays; Average radiated power; Channel capacity; Full-wave electromagnetic antenna; Information theory; Multiple input multiple output; Mutual coupling effects; Network theory analysis; Path-based channel model; Power constraint; Receive vectors; Scattering parameter matrix; Transmit vectors